Dataset to "Fluorescence Bar-coding and Flowmetry based on Dark State Transitions in Fluorescence Emitters" - Baris; Elin; Joachim; Jerker (Royal Institute of Technology, 2023)
This folder contains all raw data underlying the results presented in a manuscript, submitted for publication to Journal of Physical Chemistry B, and entitled:

Fluorescence Bar-coding and Flowmetry based on Dark State Transitions in Fluorescence Emitters

Authored by:

B. Demirbay‡, E. Sandberg‡, J. Piguet, J. Widengren*

Royal Institute of Technology (KTH), Experimental Biomolecular Physics, Dept. Applied Physics, Albanova University Center 106 91 Stockholm, Sweden

‡Contributed equally.

*Corresponding Author:

Email:  jwideng@kth.se, Phone: +46-8-7907813

The data files are grouped into the different techniques used to generate them, and refer to the figures/tables in the manuscript where the extracted results are presented.

ABSTRACT

Reversible dark state transitions in fluorophores represent a limiting factor in fluorescence-based ultrasensitive spectroscopy, is a necessary basis for fluorescence-based super-resolution imaging, but may also offer additional, largely orthogonal fluorescence-based readout parameters. In this work, we analyzed the blinking kinetics of Cyanine5 (Cy5) as a bar-coding feature distinguishing Cy5 from rhodamine fluorophores having largely overlapping emission spectra. First, fluorescence correlation spectroscopy (FCS) solution measurements on mixtures of free fluorophores and fluorophore-labeled small unilamellar vesicles (SUVs) showed that Cy5 could be readily distinguished from the rhodamines by its reversible, largely excitation-driven trans-cis isomerization. This was next confirmed by transient state (TRAST) spectroscopy measurements, determining the fluorophore dark state kinetics in a more robust manner, from how the time-averaged fluorescence intensity varies upon modulation of the applied excitation light. TRAST was then combined with wide-field imaging of live cells, whereby Cy5 and rhodamine fluorophores could be distinguished on a whole cell level, as well as in spatially resolved, multiplexed images of the cells. Finally, we established a microfluidic TRAST concept, and showed how different mixtures of free Cy5 and rhodamine fluorophores and corresponding fluorophore-labeled SUVs could be distinguished on-the-fly when passing through a microfluidic channel. In contrast to FCS, TRAST does not rely on single-molecule detection conditions or a high time-resolution and is thus broadly applicable on different biological samples. Therefore, we expect that the bar-coding concept presented in this work can offer an additional, useful strategy for fluorescence-based multiplexing, implementable on a broad range of both stationary and moving samples.
Keywords: photo-isomerization, transient state monitoring, fluorescence correlation spectroscopy, multiplexing, cellular imaging, microfluidics; Physical Sciences; Fysik